QseC sensor kinase modulates the human microbiota during enterohemorrhagic Escherichia coli O157:H7 infection in the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) - Melchior, Karine [UNESP]; Salgaço, Mateus Kawata [UNESP]; Sivieri, Katia [UNESP]; Moreira, Cristiano Gallina [UNESP] (Springer Nature, 2023)
Enterohemorrhagic Escherichia coli (EHEC) is an important gastrointestinal pathogen known for its ability to cause hemorrhagic colitis and induce hemolytic-uremic syndrome. The inner membrane QseC histidine kinase sensor has shown to be an important regulator of the locus of enterocyte effacement (LEE) island, where important EHEC key virulence genes are located. However, the QseC role during EHEC infection in human microbiota remains unknown. Herein, using the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®), we investigated whether the QseC sensor has a role in human microbiota modulation by EHEC in a dynamic model. Our data demonstrated that the QseC sensor modulates human microbiota during EHEC infection, and its absence leads to an increase in Lactobacillaceae and Bifidobacterium genus predominance, although non-effect on Bacteroides genus by EHEC strains was observed. In co-culture, the Lactobacillus acidophilus has affected EHEC growth and impaired the EHEC growth under space-niche competition, although no growth difference was observed in the QseC sensor presence. Also, differences in EHEC growth were not detected in competition with Bacteroides thetaiotaomicron and EHEC strains did not affect B. thetaiotaomicron growth either. When investigating the mechanisms behind the SHIME results, we found that hcp-2 expression for the type 6 secretion system, known to be involved in bacterial competition, is under QseC sensor regulation beneath different environmental signals, such as glucose and butyrate. Our findings broaden the knowledge about the QseC sensor in modulating the human microbiota and its importance for EHEC pathogenesis.
Keywords: Enterohemorrhagic Escherichia coli; Human intestinal microbiota; O157:H7; QseC